Choose MyPlate: Reduce Your Sodium - Ashley Hamm; Karla P. Shelnutt; Gail P. Kauwell (EDIS, 2013)
Reducing sodium intake is one of the MyPlate recommendations for healthy eating. Most Americans eat more sodium than they need, which can have negative health effects. This publication provides facts about sodium and why reducing sodium intake is important. It also provides easy tips to reduce your sodium intake. This 4-page fact sheet was written by Ashley Hamm, Karla P. Shelnutt, and Gail P. A. Kauwell, and published by the UF Department of Family Youth and Community Sciences, April 2013.